1983
DOI: 10.1677/joe.0.0960443
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroids and their relationship to binding proteins in the serum of the marmoset monkey (Callithrix jacchus)

Abstract: A sex hormone binding globulin (SHBG) similar to human SHBG was identified in marmoset serum based on its gel electrophoretic mobility, isoelectric point and steroid binding properties. Levels of serum SHBG were measured in immature and mature males, immature females and females during the luteal phase and pregnancy; serum progesterone, 5 alpha-dihydrotestosterone (5 alpha-DHT), testosterone, oestradiol-17 beta and oestrone were also measured. Mean (+/- S.E.M.) concentrations of SHBG in immature males (336 +/-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 6 publications
1
20
0
Order By: Relevance
“…Marmosets have been shown to have sex hormone binding globulin. Although Hodges et al (1983) reported low free testosterone levels (approximately 1.7-4.5%) in marmoset serum, Lunn et al (1997) more recently demonstrated higher levels of biologically active testosterone. Pugeat et al (1984) reported that plasma testosterone-estradiol binding protein in New World monkeys (including marmosets) has a low affinity despite high binding capacity for testosterone, resulting in high levels of unbound plasma testosterone in New World monkeys (20-40 ng/dl), as compared to those in Old World monkeys (3-9 ng/dl) or humans (10 ng/dl).…”
Section: Discussionmentioning
confidence: 97%
“…Marmosets have been shown to have sex hormone binding globulin. Although Hodges et al (1983) reported low free testosterone levels (approximately 1.7-4.5%) in marmoset serum, Lunn et al (1997) more recently demonstrated higher levels of biologically active testosterone. Pugeat et al (1984) reported that plasma testosterone-estradiol binding protein in New World monkeys (including marmosets) has a low affinity despite high binding capacity for testosterone, resulting in high levels of unbound plasma testosterone in New World monkeys (20-40 ng/dl), as compared to those in Old World monkeys (3-9 ng/dl) or humans (10 ng/dl).…”
Section: Discussionmentioning
confidence: 97%
“…Progesterone concentrations were determined in petroleum ether-extracted urine (50-100 pi) and plasma samples (20-40 µ ) by radioimmunoassay without chromatography (Hodges et al, 1983), using WHO CHW1 anti-progesterone antibody. The sensitivity limit of the assay (determined as 90% binding) was 10 pg/tube.…”
Section: Methodsmentioning
confidence: 99%
“…Blood samples (up to 0.3 ml) were taken from the femoral vein of the oldest daughters using the method described by HEARN and LUNN (1975). After centrifuging, the plasma samples were assayed for progesterone using a radioimmunoassay which has been validated for use on the common marmoset (HODGES et al, 1983) with modifications as described by KENDRICK and DIxsoN (1983). The precision of the assay expressed as inter-and intra-assay coefficients of variation of repeated determinants of a marmoset plasma pool were 14.8 ~o (N ----9) and 5.1 ~ (N = 10), respectively.…”
Section: Methodsmentioning
confidence: 99%